Azithromycin use and outcomes in patients with COVID-19: an observational real-world study. (November 2022) - Antonazzo, Ippazio Cosimo; Fornari, Carla; Rozza, Davide; Conti, Sara; di Pasquale, Raffaella; Cortesi, Paolo; Kaleci, Shaniko; Ferrara, Pietro; Zucchi, Alberto; Maifredi, Giovanni; Silenzi, Andrea; Cesana, Giancarlo; et al.
Highlights: The beneficial effect of azithromycin in patients with COVID-19 is debated Azithromycin was associated with a 1.5-fold higher risk of hospitalization in patients with COVID-19 Results did not indicate any significant risk reduction in the other studied outcomes Results raise concerns on risks associated with inappropriate use of azithromycin Abstract: Objectives: Previous studies ruled out the benefits of azithromycin for treatment of patients with COVID-19 who are hospitalized. However, the effects of azithromycin for treatment of patients with positive SARS-CoV-2 test results in the community remains a matter of debate. This study aimed to assess whether azithromycin, when used in subjects with positive test results for SARS-CoV-2, is associated with a reduced risk of hospitalization, in-hospital COVID-19 outcomes, and death. Methods: Two study cohorts were selected. Cohort A included subjects with positive test results for SARS-CoV-2 between February 20, 2020 and December 10, 2020; cohort B included subjects infected with SARS-CoV-2 and hospitalized between February 20, 2020 and December 31, 2020. We compared the risk of hospitalization, intensive care unit access, need for mechanical ventilation, and death in azithromycin users versus nonusers. A clustered Fine-Gray analysis was employed to assess the risk of hospitalization; logistic and Cox regressions were performed to assess the risk of intensive care unit access, mechanical ventilation, and death. Results: In cohort A, among 4861 azithromycin users and 4861 propensity-matched nonusers, azithromycin use was associated with higher risk of hospitalization (hazard ratio [HR] 1.59, 95% confidence interval [CI] 1.45-1.75) compared with nonuse. In cohort B, among 997 subjects selected in both groups, azithromycin use was not significantly associated with intensive care unit access (odds ratio [OR] 1.22, 95% CI 0.93-1.56), mechanical ventilation (OR 1.30, 95% CI 0.99-1.70), 14-day mortality (HR0.88, 95% CI 0.74-1.05), or 30-day mortality (HR 0.89, 95% CI 0.77-1.03). Conclusion: Our findings confirm the lack of benefits of azithromycin treatment among community patients infected with SARS-CoV-2, raising concern on potential risks associated with its inappropriate use.